Physicochemical Characteristics and Antidiabetic Potential In Vitro of Analog Rice Based on White Greater Yam (Dioscorea alata) and Yellow Pumpkin (Cucurbita maxima) - Imama, Darus Dina; Triwitono, Priyanto; Saputra, Wahyu Dwi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disease characterized by the presence of increased blood sugar due to insulin resistance and β-cell dysfunction maintaining the body homeostasis by lowering blood sugar levels. People with T2DM are advised to avoid consuming foods that can trigger an increase in blood sugar levels. However, daily consumption of Indonesians still depends on ordinary rice, which has a high glycemic index and can increase blood sugar levels. This shows the need to produce substitute such as analog rice, which is safe to consume by people with T2DM. Analog rice is artificial product that uses raw materials from grains or tubers. Therefore, this research aimed to produce high-antioxidant analog rice by using white greater yam and yellow pumpkin as the main ingredients. The results showed that increasing the concentration of yellow pumpkin caused a rise in physical properties such as water absorption and b value, which was the yellow color appearing in analog rice. Chemical properties such as water content, ash, and protein were increasing but starch, carbohydrates, amylose, and amylopectin levels decreased. Total phenolics, DPPH, and ABTS antioxidants, the percentage of inhibition activity of α-amylase enzyme, and descriptive sensory tests including appearance, aroma, texture, and flavor also showed an increase. The best formula was obtained in P1 treatment comprising 85% white greater yam and 15% yellow pumpkin. Specifically, P1 showed % α-amylase inhibition activity of 42%, DPPH antioxidant activity 82.39%, ABTS 86.47%, and a favorability test value of 4. This value was considered neutral, showing the potential to be well-received by panelists.